The Effectiveness of Using Crossword Puzzle Game Towards Students’ Vocabulary Mastery - Syavira Wahidah Alfaini; Sayid Ma’rifatulloh (University of Surakarta, 2023)
This study sought empirical proof of the effectiveness of using crossword puzzle games to help students in class VIIB of SMPN 1 Diwek learn vocabulary during the academic year 2022–2023. Pre-experimental design and quantitative methodology were utilized in this study's research design. Students in class VIIB are the sample in this study. According to the research findings, there is a noticeable difference in students' vocabulary proficiency before and after using crossword puzzle games to teach them. The outcome of the descriptive statistics revealed that (85.78 > 69.53) the mean score of the students' posttest was higher than the mean score of their pretest. Additionally, the results of this research were calculated using the paired sample t-test. The outcome is a significance value between 0.000 and 0.05. It denotes acceptance of the alternative hypothesis (H1) and rejection of the null hypothesis (H0). Thus, it can be stated that employing crossword puzzle games to teach kids vocabulary is beneficial because there is a noticeable change in their vocabulary achievement before and after the application of the strategy.